2016
DOI: 10.1515/mammalia-2014-0004
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, genetics and echolocation calls of the genus Kerivoula (Chiroptera: Vespertilionidae: Kerivoulinae) in Thailand

Abstract: Following extensive field work in Thailand

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…However, Khan et al [ 169 ] recognised only a single form across Malaysia (Peninsular and Borneo) and suggested that the Bornean form is a result of chromosomal polymorphism. Douangboubpha et al [ 170 ] reported that specimens from Thailand referred as K . hardwickii can be divided into two morphotypes: “flat” skulls and “domed” skulls.…”
Section: Checklist Of Bat Species In Peninsular Malaysiamentioning
confidence: 99%
See 2 more Smart Citations
“…However, Khan et al [ 169 ] recognised only a single form across Malaysia (Peninsular and Borneo) and suggested that the Bornean form is a result of chromosomal polymorphism. Douangboubpha et al [ 170 ] reported that specimens from Thailand referred as K . hardwickii can be divided into two morphotypes: “flat” skulls and “domed” skulls.…”
Section: Checklist Of Bat Species In Peninsular Malaysiamentioning
confidence: 99%
“…Ellerman and Morrison-Scott [ 138 ] recognised four subspecies: hardwickii (type locality: Java), depressa (type locality: southern Burma = Myanmar), crypta (type locality: southern India), and malpasi (type locality: Sri Lanka) whereas Hill [ 171 ] recognised five, including engana (type locality: southwest of Sumatra). The names hardwickii and depressa were suggested for the specimens from Thailand with “domed” and “flat” skulls respectively, but further research is required to assign Linnaean names conclusively [ 170 ]. Whether the four BINs in our NJ tree ( Fig 6 ) represent the four subspecies remains to be determined.…”
Section: Checklist Of Bat Species In Peninsular Malaysiamentioning
confidence: 99%
See 1 more Smart Citation
“…Bats in the genus Kerivoula generally have relatively short, highpitched calls [18] covering a very large bandwidth, which further increases when they approach an object [19]. Such a call design is typical for the guild of narrow-space gleaning foragers [20] as it facilitates hunting in dense vegetation [19,20].…”
Section: Do Pitcher Plants Have Ultrasound Reflectors?mentioning
confidence: 99%
“…Additionally, we included several species that occur near the Philippines, including K. titania, K. intermedia, and K. minuta. We did not include several members of the K. hardwickii group, a complex that requires much detailed study (e.g., K. depressa, K. krauensis, K. furva or K. kachinensis; see Bates et al 2007;Francis et al 2007;Khan et al 2010;Douangboubpha et al 2015;Son et al, et al 2015;Struebig et al 2016;Kuo et al 2017;Tu et al 2018).…”
Section: Introductionmentioning
confidence: 99%